Applying analytic network process (ANP) to rank critical success factors of waterfront redevelopment. (1st January 2013) - Lee, Paul Tae-Woo; Wu, Jei-Zheng; Hu, Kai-Chieh; Flynn, Matthew
Waterfront redevelopment (WFD) is not only driven by several external forces such as changes of port function, conflicts between port authority and local government, environmental issues caused by port activities, and the bad public image of ports, but also coincides with an increasing consciousness and assertiveness by individuals in their consumption lifestyles. With attention on the conflicting demands and needs of WFD stakeholders and interdependence of their concerns, this paper applies an analytic network process (ANP) to rank the critical success factors of WFD by comparing the preferences of decision-makers and stakeholders. An efficient questionnaire is designed to compare analytic hierarchy process (AHP) and ANP. The questionnaire was dispatched to experts and stakeholders in WFD. For ANP results, the top five were connectivity, maritime clustering, transformation of port/city interface, accessibility, and port infrastructure, which were different from AHP outcomes. Case study research by the authors supports the results of ANP.